Specific impacts of climate change on the hydrological patterns and land use dynamics in the Arghandab River Basin, Kandahar, Afghanistan - Bashir Ahmad Karimi; Mohammad Aslam Haziq; Athiqullah Hayat (Natural Hazards Research)
Changes in rainfall patterns and warming temperatures brought on by greenhouse gas emissions have significant impact on the global hydrological cycle. The deteriorating physical properties of river basins, melting glaciers, drought conditions, food shortages, extreme weather events, and alterations in groundwater recharge are all consequences of these changes. Climate change and global warming have placed a greater strain on the climatic factors affecting the Arghandab River Basin. Sustainable development in the basin's depends on assessment of the long-term outcomes of climate change on several characteristics of the basin. The primary goal is to understand the average general hydrology of the basin. Furthermore, based on that, assess the impacts of climate change on temperature and precipitation Next, evaluate the work done to simulate and model surface runoff and sediment transport in order to understand the impacts of climate change on these processes, as well as the temporal variations and alterations in land use and land cover due to climate change. Data were collected from regional and international data sets. The soil and water assessment tool (Swat, 2012) model was applied to assess the average general hydrology and sediment transport of the basin, and statistics were used to estimate the amount of change. The research found that this basin is highly sensitive to climate change. The results indicate that from 1981 to 2021, the historic temperature increased by 1.41 ​°C, while average yearly precipitation and runoff decreased by 7.72%. Conversely, evapotranspiration rose by 7.54%. Additionally, shrubland expanded by 2.28%, grassland increased by 12.9%, and barren areas decreased by 15.23%. Such alterations directly affect water availability for agriculture and other essential uses, exacerbating vulnerability to natural hazards. Future research should focus on developing targeted adaptation strategies for the Arghandab River Basin, emphasizing the need for integrated water management practices and innovative groundwater recharge techniques to mitigate the impacts of climate change.